2016
DOI: 10.1038/srep36868
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of oncogenic RAS and c-Myc expression in MOLT-4 leukaemia cells by a salicylaldehyde semicarbazone copper(II) complex

Abstract: Copper complexes with potent anti-tumor effect have been extensively developed. Most investigations of their modes of action focused on the biomolecular targets but not the signal transduction between target binding and cell death. We have previously shown that the cytotoxic complex pyridine(2,4-dihydroxybenzaldehyde dibenzyl semicarbazone)copper(II) (complex 1) shows selective binding to human telomeric G-quadruplex DNA over double-stranded DNA in vitro. Herein, we elucidate the mechanism of action by which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The mechanism described in this study suggested more extensive roles for G4 regulation in complicated antitumor therapies. 92 Similar to the idea of targeting and manipulating multiple G4 targets, some strategies that simultaneously targeted G4 motifs and the i-motif have also been reported recently. It is known that G4s are not the only secondary structures in cells; hairpin structures, for example, are common.…”
Section: Ligands Targeting Promoter G4s and Transcriptional Regulationmentioning
confidence: 94%
“…The mechanism described in this study suggested more extensive roles for G4 regulation in complicated antitumor therapies. 92 Similar to the idea of targeting and manipulating multiple G4 targets, some strategies that simultaneously targeted G4 motifs and the i-motif have also been reported recently. It is known that G4s are not the only secondary structures in cells; hairpin structures, for example, are common.…”
Section: Ligands Targeting Promoter G4s and Transcriptional Regulationmentioning
confidence: 94%
“…In Goh et al . (2016), a salicylaldehyde semicarbazone copper (II) complex induced apoptosis through the caspase-dependent pathway by reducing the expression of RAS and MYC , and by inhibiting Ras-ERK and PI3K-Akt pathways in MOLT-4 leukemia cells 48 . In 2013, Shen and colleagues proved that a G4 ligand named SYUIQ-FM05 suppressed KIT mRNA transcription and total kit protein amount in K562 cells, and this inhibition led to a downregulation of MEK activity, ERK phosphorylation, and the RAS/MEK/ERK signaling pathway 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Small molecules that stabilize one of the possible 3D shapes of the G-quartets have been hypothesized as tools for antineoplastic function, for example, to block promoters containing tetraplex consensus [ 14 16 ]. The oncogenes c-myc, bcl2, and kRAS, the dystrophy gene DMPK, the transcription factor Oct4, and the topoisomerase-1 are all putative targets of those tetraplex-interacting molecules as part of potential clinical care [ 17 20 ]. TMPyP4 is one of those molecules, as it is a cationic porphyrin that is known mainly as a DNA tetraplex stabilizer, which is largely used for in vitro analysis [ 21 ].…”
Section: Introductionmentioning
confidence: 99%